Clonal evolution: a landmark of MPN evolution - Maslah, Nabih; Giraudier, Stephane; Cassinat, Bruno; Kiladjian, Jean-Jacques (Frontiers in Hematology, 2024)
Myeloproliferative Neoplasms comprise a heterogeneous group of diseases characterized over the past two decades by the acquisition of somatic mutations in hematopoietic stem cells, leading to a pre-leukemic state. The natural history of the disease is marked by the sequential acquisition of genetic events that play an essential role in the phenotype, evolution and response to treatment of the disease. Indeed, disease progression is as heterogeneous as the variety of genetic abnormalities found in individual patients, some of whom lead to disease evolution with a pejorative prognosis, while others persist in a benign manner. In order to better explore these questions, it is important to better understand: (1) the genetic structure of the tumor through dynamic reconstruction of clonal architecture (2) the factors favoring the development of certain clones and their expansion, some of which are governed by Darwinian laws. These parameters could help explain the heterogeneity between MPN patients with similar genetic profiles, and prevent the emergence of clones identified as aggressive by the use of innovative therapeutic strategies targeting new pathways to prevent early transformations in poor prognosis MPN subtypes.